Phylogeny and evolution of antlered deer determined from mitochondrial DNA sequences. - Miyamoto, M M (1990)
Mitochondrial DNA sequences of both ribosomal RNA genes and three adjacent transfer RNA genes were obtained for the three extant subfamilies of antlered deer (Cervinae, Muntiacinae, and Odocoileinae) as well as for their antlerless sister group Hydropotinae (family Cervidae). Phylogenetic analysis of these sequences (each nearly 2.7 kilobase pairs in length) supports a cervine/muntiacine clade to the exclusion of odocoileines. These results are statistically significant, stable, and congruent with some independent data. Our mitochondrial DNA sequences, when coupled with other information, indicate that the earliest fossil antlered deer are not closely related to living muntiacines or any other contemporary subfamily. From this information, we hypothesize an Old World, Late Miocene origin of Odocoileinae.